X-fever, water free cold sponge - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Muhammad Umer, Khan; Mohammad Ahmed, Isa (2018)
Traditional and historical methods to decrease body temperature during high fever and injury treatment have been implemented since nineteen century. These old methods though are effective but require better management, when it comes to use of water and to dry water, when subjected to patient. Beside the application of water at room temperature to various subjects at lower temperature for a better prognosis is also questionable Best way is 10 provide local solution to global problem. We have made use of Malaysian Hibiscus sabdariffa L. powder for developing a new product, by using traditional leaf, herbs aml Hibiscus flowers. H. sabdariffa L. (Roselle; Malvaceae) is the most traded medicinal and commercial plants worldwide. In the tropical countries, Roselle is the major flavoring agent. We have designed and developed the reusable cold pack consisting of Hibiscus powder, gelatin. water and ethanol with specific ratios. The mixture was enveloped in a specially selected flexible membrane composed of flexible plastic molecules. A total of 200 subjects were tested for quality of this product. The effects were found significant (98%). Showed to be very effective specially for longtime preserving of the low temperature up to 10 hours compared with controls. X fever has shown not to only decrease temperature but to also absorb heal. This makes it versatile, cost effective traditional herb based easy to produce product. The incorporation of digital technology brings it to new level of temperature monitoring devices.